Influence of phosphate supply on teichoic acid and teichuronic acid content of Bacillus subtilis cell walls. - Lang, W K (1982)
Bacillus subtilis 168 was grown in chemostat culture in fully defined media containing a constant concentration of magnesium and concentrations of phosphate that varied from those giving phosphate-limited growth to those in which phosphate was present in excess and magnesium was limiting. Phosphate-limited bacteria were deficient in wall teichoic acid and contained less than half as much cellular phosphate as did bacteria grown in excess of phosphate. Approximately 70% of the additional phosphate in the latter bacteria was present as wall teichoic acid, indicating that the ability of the bacteria to discontinue teichoic acid synthesis when grown under phosphate limitation permits a substantial increase in their growth yield. Since not all of the additional phosphate is present as wall teichoic acid other cellular phosphates may also be present in reduced amounts in the phosphate-limited bacteria. The content of phosphate groups in walls of magnesium-limited bacteria was similar to the content of uronic acid groups in walls of phosphate-limited bacteria, and walls of bacteria grown in media of intermediate composition contained intermediate proportions of the two anionic polymers. Phage SP50, used as a marker for the presence of teichoic acid, bound densely to nearly all of the bacteria in samples containing down to 22% of the maximum content of teichoic acid. Apparently, therefore, nearly all of these bacteria contain teichoic acid, and the population does not consist of a mixture of individuals having exclusively one kind of anionic polymer. Bacteria containing less than 22% of the maximum content of teichoic bound in a nonuniform manner, and possible explanations for this are discussed.